Synthesis of 2-benzyl N-substituted anilines via imine condensation–isoaromatization of (E)-2-arylidene-3-cyclohexenones and primary amines - Li, Lu; Li, Na; Mo, Xiao-Tian; Yuan, Ming-Wei; Jiang, Lin; Yuan, Ming-Long (Beilstein Journal of Organic Chemistry, 2024)
A catalyst- and additive-free synthesis of 2-benzyl N-substituted anilines from (E)-2-arylidene-3-cyclohexenones and primary amines has been reported. The reaction proceeds smoothly through a sequential imine condensation–isoaromatization pathway, affording a series of synthetically useful aniline derivatives in acceptable to high yields. Mild reaction conditions, no requirement of metal catalysts, operational simplicity and the potential for scale-up production are some of the highlighted advantages of this transformation.
Keywords: aniline; (E)-2-arylidene-3-cyclohexenone; imine condensation; isoaromatization; primary amine